Mobile Phone Brand Categorization vs. Users’ Security Practices - Androulidakis, I.; Kandus, G. (Engineering, Technology & Applied Science Research, 2011)
In the present paper, we correlated the brand of mobile phone to users’ security practices, statistically processing a large pool of the responses of 7172 students in 17 Universities of 10 Eastern and Southern Europe countries. Users show different behavior in an array of characteristics, according to the brand of the mobile phone they are using. As such, there is a categorization of areas, different for each brand, where users are clearly lacking security mind, possibly due to lack of awareness. Such a categorization can help phone manufacturers enhance their mobile phones in regards to security, preferably transparently for the user.